STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) STUDI KASUS PADA TOKO MERDEKA SANGATTA KABUPATEN KUTAI TIMUR - Iwan Saputra; Mihani; Simunawir Sitoro (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
This research is qualitative research and survey research. The subjects of this research are consumers at the merdeka store in Kutai Regency. The data was collected using questionnaires and documentation, while the data analysis was carried out using a SWOT analysis covering Strengths, Weaknesses, Opportunities and Threats. The results showed that: The main strength at the Merdeka Sangatta Store based on the highest score was the Price of Products Sold at the Merdeka Sangatta Store which was affordable among customers, the business capital spent in accordance with the profits obtained, prioritizing the quality of product materials with the same score of 0.58